PEMBACAAN AUDIENS TENTANG DESTINASI WISATA BANDUNG - Muhammad Ray Febriano; Catur Nugroho (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
@explorebandung is an account provider of Bandung tourist destination that has the largest number of followers in Instagram. @explorebandung provides content such as interesting photos about a palce or location which can be the reference for Instagram users when travelling in Bandung. The methodologhy of this research is descriptive qualitative with Stuart Hall’s reception analysis. The purpose of this research is to know the position of audience in accordance with Stuart Hall’s three positions readout about the content of tourist destination that served in @explorebandung. These three positions are dominant reading, negotiated reading and oppositional reading. Then, researcher will measures how far the response of @explorebandung’s followers after reading Bandung tourist destinaion’s message. The result of this research shows that from the three element of tourist destination’s message in @explorebandung, three informants is in negotiated reading position on the photo’s element, while the other one is in dominant reading position. Furthermore, on the caption’s element, two informants is in dominant reading position, while the other two is in negotiated reading position. Then, on the hashtag’s element, three informants is in dominant reading position, while the other one is in negotiated reading position.